GE_GERICHTE C/13299/2014 vom 1. September 2021 - GE Cour de justice (2021)
mandat;contrat architecte global;légitimation passive;représentation de l'union conjugale;domm. int. et tort moral;calcul honoraires | CO.367.al1; CC.166.al1; CC.166.al2; CO.32ss; CO.398; CO.47; CO.99.al3; CO.394.al3